Synthesis, spectral behavior and biological activity of some novel 1,3,4-oxadiazine cyanine dyes - Shindy, Hassan Abazied; Goma, Maha Mubark; Harb, Nemat Abd El-Rahman (European Journal of Chemistry, 2015)
New methine cyanine dyes covering monomethine cyanine dyes and dimethine cyanine dyes derived from benzo[(2,3-b)benzoxazine; (2,3-e)1,3,4-oxadiazine]-5,12-dione were prepared. The electronic visible absorption spectra of all the synthesized cyanine dyes were investigated in 95% ethanol solution. Biological activity for a number of selected compounds was tested and evaluated against various bacterial strains (Bacillus subtilis, Escherichia coli, Pseudomona aeruginosa and Staphylococcus aureus). Structural determination was carried out via elemental analysis, visible, mass, IR and 1H NMR spectroscopic data.